Destabilization of Abnormal Methylation Enzymes as an Effective Therapeutic Strategy via Induction of Terminal Differentiation to Take Out Both Cancer Stem Cells and Cancer Cells - Liau, Ming C.; Fruehauf, Paul A.; Zheng, Zhong-Hui; Fruehauf, John P. (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
The objective of this study was to develop cancer drugs effective to take out both cancer stem cells (CSCs) and cancer cells, particularly CSCs since these cells stood in the way to deny the success of conventional therapies to put cancer away. The association of methylation enzymes with telomerase constitutes a unique abnormality of cancer cells. This abnormality locks methylation enzymes in an exceptionally stable and active state so that hypomethylation of nucleic acids necessary for the cells to undergo Terminal Differentiation (TD) cannot take place. Human body produces metabolites that are able to eliminate telomerase from abnormal methylation enzymes of cancer cells to allow TD to proceed. Cell Differentiation Agent-2 (CDA-2) is a preparation of human metabolites from freshly collected urine, which has been approved for cancer therapy by the Chinese FDA. The effective components of CDA-2 are Differentiation Inducers (DIs) to target on the telomerase of abnormal methylation enzymes and Differentiation Helper Inducers (DHIs) which are the inhibitors of individual enzymes of ternary methylation enzymes. CDA-2 was very effective for the therapy of Myelodysplastic Syndrome (MDS), which is a disease attributable to Cancer Stem Cells (CSCs). We have previously carried out extensive studies on the DHIs of CDA-2.We are now focusing on the DIs of CDA-2 in order to formulate synthetic CDA for the prevention and therapy of cancer via targeting of CSCs. DIs were purified from CDA-2 solution by procedures including differential solvent extraction, gel filtration, ion exchange chromatography, TLC, and HPLC. The mass of purified active preparation was determined by mass spectroscopy. DI activity was based on the Nitro Blue Tetrazolium (NBT) assay of HL-60 cells. DIs of CDA-2 were found predominantly as acidic liposomal complexes extractable by dichloromethane. A good proportion of which became covalently linked to inactive carriers which were not soluble in dichloromethane, but soluble in alcohols. We have identified pregnenolone as a DHI of active liposomal complexes. After dissociation from pregnenolone, the active DIs of CDA-2 were not associated with UV absorption peaks of HPLC. We suspected that the active DIs might be acidic peptides derived from endogenous proteins, because we have previously found that acidic peptides of CDA-2 were active DIs. We, thus, randomly picked pentapeptides containing at least two acidic amino acid residues from the sequences of \(α\)- and \(β\)-hemoglobin for synthesis to test their DI activities. Indeed, acidic pentapeptides of hemoglobin were active as DIs, although the activities were not impressive. Retinoic Acid (RA) and 12-O-TetradecanoylPhorbol-13-Acetate (TPA) are well known DIs with much better activities. In this study, we found Pyrvinium Pamoate (PP) as the best DHI, and triinosinate + tetrainosinate (I3 + I4) as an acceptable DHI. With effective DIs and DHIs on hand, our deliberated CDA formulations were as followings: for the therapy of MDS, the CDA-MDS formulation was RA(ED25)-5P-1(ED25)-I3 + I4(RI0.5)-PP(RI0.5)-sodium pregnenolone sulfate(RI0.5); for the therapy of CSCs, the CDA-CSC formulation was RA(ED25)- TPA(ED25)-PP(RI0.5)-resveratrol(RI0.5)-curcumin(RI0.5); for the therapy of brain tumor, the CDA-BT formulation was TPA(2xED25)-PP(2xRI0.5)-sodium phenylbutyrate(RI0.5)-pyrogallol(RI0.5); and for the therapy of melanoma and pancreatic cancer, the CDA-M&P formulation was RA(ED25)-TPA(2xED25)- 5P-1(ED25)-PP(2xRI0.5)-sodium tannate (RI0.5). The above CDA formulations all produced 100% NBT + on HL-60 cells. In conclusion, CDA formulations are the best to take out CSCs protected by drug resistant mechanism. A major biological mission of CSCs is to repair the wound. CDA formulations are primarily made up by DIs and DHIs which are wound healing metabolites, the partners involved in the biological mission of CSCs. Naturally, DIs and DHIs are tolerable to CSCs. CDA formulations can also induce cancer cells to undergo TD to terminate malignant growth.